2019
DOI: 10.3389/fpsyg.2019.02482
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of School Climate on Well-Being Experience and School Engagement: A Study With High-School Students

Abstract: The aim of this work is to investigate the factors promoting students’ engagement at school and supporting their well-being experience. According to the Positive Education there is a strong relationship between school environment and student’s well-being. Moreover, the quality of the school climate perceived by the students was found to influence engagement in school activities, as well. In this study, 153 students (M = 67) attending 10th grade were presented with tests and questionnaires to assess individual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
31
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 38 publications
4
31
1
1
Order By: Relevance
“…In addition, the relationship of school leaders’ perceptions with both teachers and students can contribute to design consistent schools’ policies, building trusting relationships with teachers and students, and to offer enriching activities for effectively responding to students’ needs. This is in line with recent empirical studies on well-being ( Lombardi et al, 2019 ) that emphasize the importance of integrating socio-emotional development in schools’ daily practice ( Burns and Gottschalk, 2019 ). Such type of school-level interventions, which have emerged to be more successful in some European countries including Italy ( Govorova et al, 2020 ), encompasses key components of well-being and inclusion through technologies such as relationships , school community , safety , individual learning needs , active learning , and collaboration , explored in the SELFIE self-reflection process ( Kampylis et al, 2016 , 2019 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, the relationship of school leaders’ perceptions with both teachers and students can contribute to design consistent schools’ policies, building trusting relationships with teachers and students, and to offer enriching activities for effectively responding to students’ needs. This is in line with recent empirical studies on well-being ( Lombardi et al, 2019 ) that emphasize the importance of integrating socio-emotional development in schools’ daily practice ( Burns and Gottschalk, 2019 ). Such type of school-level interventions, which have emerged to be more successful in some European countries including Italy ( Govorova et al, 2020 ), encompasses key components of well-being and inclusion through technologies such as relationships , school community , safety , individual learning needs , active learning , and collaboration , explored in the SELFIE self-reflection process ( Kampylis et al, 2016 , 2019 ).…”
Section: Discussionsupporting
confidence: 88%
“…In particular, the strong relationships that emerged between students and teachers, and between teachers and school leaders highlight the importance of considering the perceptions of all the three main actors in the school community to promote wellbeing and inclusion (Kampylis et al, 2015;OECD, 2019). This is in line with the evidence that school climate is as an important factor to be considered to improve engagement in school activities, but it is effective only when its influence can modify the well-being experience of the students (Lombardi et al, 2019).…”
Section: Discussionsupporting
confidence: 87%
“…The creation of this construct has received attention as a way of improving academic performance (Cocorada et al, 2017;Bravo-Sanzana et al, 2019b;Laurito et al, 2019), reducing problem behaviors (Cornell and Huang, 2016;Gaias et al, 2017;Konold et al, 2017;Moratto et al, 2017;Valdés-Cuervo et al, 2018), developing environments with a lower perception of stress and greater effectiveness and job satisfaction among teachers (Malinen and Savolainen, 2016;Bravo-Sanzana et al, 2019a), and especially recognizing the impact of school climate on wellbeing experience and school engagement (Lombardi et al, 2019). Likewise, school climate is important for promoting student life satisfaction and for preventing the negative consequences associated with being bullied (Lázaro-Visa et al, 2019), as well as the association between SSC and school mental health.…”
Section: Introductionmentioning
confidence: 99%
“…However, in one exploratory study, authors demonstrated that school connectedness partially mediated the association between emotional distress and school engagement which pertained to educational attainment and school performance [14]. Additionally, other studies also reported the association of other indices of school social capital, such as sense of belonging, support from peers and teachers, and safety, with HRQOL [15][16][17]. Studies have suggested that these indices are malleable and thus can be modifiable factors [18,19].…”
Section: Introductionmentioning
confidence: 98%